2003
DOI: 10.1002/cne.10876
|View full text |Cite
|
Sign up to set email alerts
|

Central projections of the saccular and utricular nerves in macaques

Abstract: The central projections of the utricular and saccular nerve in macaques were examined using transganglionic labeling of vestibular afferent neurons. In these experiments, biotinylated dextran amine was injected directly into the saccular or utricular neuroepithelium of fascicularis (Macaca fascicularis) or rhesus (Macaca mulatta) monkeys. Two to 5 weeks later, the animals were killed and the peripheral vestibular sensory organs, brainstem, and cerebellum were collected for analysis. The principal brainstem are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
64
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 101 publications
(65 citation statements)
references
References 103 publications
1
64
0
Order By: Relevance
“…In squirrel monkeys, Naito et al (1995) did not see a projection to Y from the utricle, nor was this connection seen in the guinea pig (Gstoettner et al, 1992). The same BDA technique described in this report (Newlands et al, 2001) has demonstrated utricular and saccular projections to Y in macaques.…”
Section: Vestibular Nuclei Projectionssupporting
confidence: 55%
“…In squirrel monkeys, Naito et al (1995) did not see a projection to Y from the utricle, nor was this connection seen in the guinea pig (Gstoettner et al, 1992). The same BDA technique described in this report (Newlands et al, 2001) has demonstrated utricular and saccular projections to Y in macaques.…”
Section: Vestibular Nuclei Projectionssupporting
confidence: 55%
“…6,7 Polysynaptic pathways also have a critical role in mediating the utriculo-ocular reflex. [8][9][10] Signals from the lateral utricle ipsilateral to the direction of head translation are transmitted to the ipsilateral vestibular nucleus, via an extensive network of projections within the cerebellum (including the nodulus, ventral uvula, fastigial nucleus, anterior vermis, and flocculus/ventral paraflocculus). Polysynaptic pathways are also responsible for generating ocular counterroll movements during static head tilt.…”
Section: Anatomy and Physiology Of The Otolithsmentioning
confidence: 99%
“…This test measures the ability to learn, sustain, and execute complex coordinate movements, processes in which the cerebellum and its processing of incoming and outgoing signals plays a crucial role. In this context, it is interesting that other Foxs1-positive regions, such as the fastigial nucleus, vestibular nuclei, and external cuneate nucleus, have been implicated as targets for cerebellar projections (37,45). Thus, it is possible that alterations in processing and integration of cerebellar afference/ efference, at several levels, might be altered in response to lack of Foxs1, rendering null mutants more capable in the rotarod test.…”
Section: Vol 25 2005mentioning
confidence: 99%